Improvement of hyperuricemia in chronic hepatitis C patients receiving directly acting antiviral agents. Issue 3 (10th September 2019) - Jang, Tyng‐Yuan; Huang, Ching‐I; Yeh, Ming‐Lun; Liang, Po‐Cheng; Tsai, Pei‐Chien; Lin, Yi‐Hung; Hsieh, Ming‐Yen; Hou, Nai‐Jen; Lin, Zu‐Yau; Chen, Shinn‐Cherng; Huang, Jee‐Fu; Dai, Chia‐Yen; et al.
Abstract: Background and Aim: Hepatitis C virus eradication via the use of antivirals ameliorates metabolic profiles. The changes in serum uric acid (SUA) levels in chronic hepatitis C patients who receive antivirals are not well understood. We aimed to address this issue by comparing the SUA changes before and after the achievement of a sustained virological response (which is defined as hepatitis C virus RNA seronegativity at 12 weeks after the end of treatment). Methods: Two hundred and thirteen sustained virological response patients who were treated by directly acting antivirals were consecutively enrolled. Pretreatment and post‐treatment SUA levels were compared. Hyperuricemia was defined as a uric acid level > 7.0 mg/dL in men and > 6.0 mg/dL in women. Results: The SUA levels significantly decreased after treatment, as compared to the pretreatment levels (5.6 ± 1.5 vs 6.0 ± 1.7 mg/dL, respectively; P  < 0.001). The proportion of hyperuricemia incidences significantly decreased after treatment (25.8% vs 35.7%, respectively; P  = 0.001). The improvement was only observed in patients with a fibrosis‐4 index (FIB‐4) < 6.5 (25.7% vs 37.1%, P  = 0.001) but not in those patients with a FIB‐4 ≧ 6.5 (26.3% vs 28.9%, P  = 1.00). A multivariate analysis revealed that the factor that was associated with significantly decreased SUA levels was FIB‐4 < 6.5 (odds ratio [OR]/95% confidence interval [CI]: 3.22/1.04–9.95, P  = 0.04) and estimated glomerular filtration rate < 60 mL/min/1.73 m 2 (OR/CI: 4.34/1.94–9.73, P  < 0.001). There existed a trend of a higher proportion of patients with significant SUA improvement along with the decrement of FIB‐4 (29.7%, 25%, and 10.5% in patients with FIB‐4 < 3.25, 3.25–6.5, and > 6.5, respectively; trend P  = 0.03). Conclusions: SUA levels were significantly decreased in chronic hepatitis C patients after viral eradication. The improvement was particularly enhanced in patients with mild liver disease.